2021
DOI: 10.1371/journal.pone.0256822
|View full text |Cite
|
Sign up to set email alerts
|

Privacy nudges for disclosure of personal information: A systematic literature review and meta-analysis

Abstract: Objective Digital nudging has been mooted as a tool to alter user privacy behavior. However, empirical studies on digital nudging have yielded divergent results: while some studies found nudging to be highly effective, other studies found no such effects. Furthermore, previous studies employed a wide range of digital nudges, making it difficult to discern the effectiveness of digital nudging. To address these issues, we performed a systematic review of empirical studies on digital nudging and information discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 99 publications
2
6
0
Order By: Relevance
“…The difference between the two nudges might be due to the fact that user disclosure is an intrinsic behavior and people do not make judgments about their privacy based on what others do. These results come to complement previous research [97,114,115] on nudging and privacy for the disclosure of personal information online (not just specific to chatbots). Overall, empirical research on digital nudging to alter users' disclosure behaviors has produced conflicting findings in the past, with some studies finding it to be quite effective while others have found no such results [97].…”
Section: Theoretical Contributionssupporting
confidence: 86%
See 3 more Smart Citations
“…The difference between the two nudges might be due to the fact that user disclosure is an intrinsic behavior and people do not make judgments about their privacy based on what others do. These results come to complement previous research [97,114,115] on nudging and privacy for the disclosure of personal information online (not just specific to chatbots). Overall, empirical research on digital nudging to alter users' disclosure behaviors has produced conflicting findings in the past, with some studies finding it to be quite effective while others have found no such results [97].…”
Section: Theoretical Contributionssupporting
confidence: 86%
“…These results come to complement previous research [97,114,115] on nudging and privacy for the disclosure of personal information online (not just specific to chatbots). Overall, empirical research on digital nudging to alter users' disclosure behaviors has produced conflicting findings in the past, with some studies finding it to be quite effective while others have found no such results [97]. On one hand, studies have demonstrated that motivating communications and persuasive messages with stronger arguments or more positive framings can enhance the disclosure of private information [114,116].…”
Section: Theoretical Contributionssupporting
confidence: 86%
See 2 more Smart Citations
“…In the context of information disclosure, these two theories have been used to examine individuals' willingness to disclose personal information via technology such as IoT-enabled smart applications (Zhang et al ., 2023), AI-powered smart hospital (Jia et al ., 2022), online banking subscriptions (Njenga and Ndlovu, 2012), and intelligent machines (Majeed and Hwang, 2023). When used in conjunction, PCT and TAM highlight the importance of perceived benefits and trust in shaping individuals' willingness to disclose information (Ioannou et al ., 2021). In the context of caregiver robots, PCT and TAM were employed to develop an integrative nomological network to investigate the user's willingness to disclose the PHI required to use the robots.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%